(untitled) (Baghdad Science Journal, 2023)
Development of a precise and delicate reaction has been acquired for the determination of vancomycin hydrochloride using batch and cloud point extraction (CPE) methods. The first method is based on the formation of azo dye as a result of diazotized dapsone coupled with vancomycin HCl (VAN) in a basic medium. The sensitivity of this reaction was enhanced by utilizing a nonionic surfactant (Triton X-114) and the cloud point extraction technique (second method). The azo dye formed was extracted into the surfactant-rich phase, dissolved in ethanol and detected at λmax 440 nm spectrophotometrically. The reaction was investigated using both batch and CPE methods (with and without extraction), and a simple comparison between the two developed methods was made. The conditions that affect the extraction process and the sensitivity of the methods have been carefully examined. The linearity of the calibration curves was in the range of 3-50 and 0.5- 25 µg.mL-1 with limits of detection of 0.806 and 0.462 µg.mL-1 for VAN in both batch and CPE procedures, respectively. The percentage of relative standard deviation (R.S.D.%) for the two methods was better than 2.54% and 2.83%, respectively. The recommended procedures have been effectively used to assay VAN in commercial injections.